Detection of Amantadine-Resistant Influenza A Virus Strains in Nursing Homes by PCR-Restriction Fragment Length Polymorphism Analysis with Nasopharyngeal Swabs - Saito, Reiko (American Society for Microbiology, 2002)
Annual consumption of amantadine increased abruptly after its approval for the treatment of influenza A virus infections in Japan in 1998, and the emergence of amantadine-resistant viruses is now a matter of concern. To detect resistant influenza A virus strains, we have developed a PCR-restriction fragment length polymorphism (PCR-RFLP) analysis for nasopharyngeal swabs. Three different primer sets for nested PCR were designed to incorporate restriction sites into the amplicon to differentiate single-amino-acid substitutions at positions 27, 30, and 31 that confer resistance in the transmembrane domain of the M2 protein. Each PCR product was digested with respective endonucleases (BspLU11I for amino acid change at position 27, HhaI for position 30, and ScaI for position 31), and the polymorphisms were determined by electrophoresis. Thirty-four (24.1%) of 141 PCR-positive samples had resistance patterns in eight nursing homes in the 1998–1999 season. Thirty-one viruses (91.2%) showed a change at position 31 (serine to asparagine), three viruses (8.8%) showed a change at position 30 (alanine to threonine), and none showed a change at position 27. The incidence of resistant viruses did not show any significant difference between four facilities where amantadine was used mainly for influenza treatment and four other facilities where it was used only for Parkinson’s disease, values being 27.6 and 16.3%, respectively. We have confirmed that the PCR-RFLP method is useful for detecting amantadine-resistant strains directly from nasopharyngeal swabs and that resistant viruses were circulating in nursing homes where the drug was used not only for influenza virus but also for Parkinson’s disease.